A review of chimeric antigen receptor T-cells in lymphoma. Issue 7 (3rd July 2019) - Anderson, Jennifer Kelly; Mehta, Amitkumar
ABSTRACT: Introduction : Immunotherapy has revolutionized the treatment of cancer. Antibodies, antibody drug conjugates, and bispecific antibodies have improved outcomes in various cancers especially lymphomas. Chimeric antigen receptor T cell (CAR-T) is a step forward in the immunotherapy paradigm for the treatment of Lymphomas. Recently, two CAR-T products, Tisagenlecleucel and Axicabtagene ciloleucel, were approved by the US FDA. While it is exciting to have such novel treatment available, the challenges of production, administration, related toxicity, and cost remain. Specific toxicities related to CAR-T like Cytokine Release Syndrome (CRS) and Immune Effector Cell-Associated Neurotoxicity Syndrome (ICANS) could be fatal and need close monitoring and prompt treatment to avoid mortality and improve efficacy of the treatment. Areas covered : In this article, the authors discuss receptor constructs, administration, toxicities, efficacy and reimbursement of CAR-T treatment. Expert opinion : Since approval of CAR-T treatment, cost of therapy and reimbursement have been a big challenge in implementation of CAR-T. This has triggered cost-effective analysis and nationwide discussions about the reimbursement process of such treatment. In spite of these challenges, CAR-T treatment is a huge step forward with a very bright future. Novel CAR-T targeting a variety of antigens in different cancers seems promising in near future.